Reentrant para‐Hisian ventricular tachycardia eliminated from the noncoronary cusp: Importance of regional anatomy for vantage‐point ablation. (4th March 2020) - Nishimura, Takuro; Kannan, Arun; Tung, Roderick
Abstract: We present a rare case of reentrant ventricular tachycardia proven by entrainment maneuvers that was successfully ablated from the noncoronary cusp. The case highlights regional anatomy, pacing maneuvers with multi‐modality images from fluoroscopy, intracardiac echo, and electroanatomical mapping.